Endothelial to mesenchymal transformation is induced by altered extracellular matrix in aortic valve endothelial cells. Issue 10 (27th June 2017) - Dahal, Sudip; Huang, Peter; Murray, Bruce T.; Mahler, Gretchen J.
Abstract: Alterations in shear stress, mechanical deformation, extracellular matrix (ECM) composition and exposure to inflammatory conditions are known to cause endothelial to mesenchymal transformation (EndMT). This change in endothelial phenotype has only recently been linked to adult pathologies such as cancer progression, organ fibrosis, and calcific aortic valve disease; and its function in adult physiology, especially in response to tissue mechanics, has not been rigorously investigated. EndMT is a response to mechanical and biochemical signals that results in the remodeling of underlying tissues. In diseased aortic valves, glycosaminoglycans (GAGs) are present in the collagen‐rich valve fibrosa, and are deposited near calcified nodules. In this study, in vitro models of early and late‐stage valve disease were developed by incorporating the GAGs chondroitin sulfate (CS), hyaluronic acid, and dermatan sulfate into 3D collagen hydrogels with or without exposure to TGF‐β1 to simulate EndMT in response to microenvironmental changes. High levels of CS induced the highest rate of EndMT and led to the most collagen I and GAG production by mesenchymally transformed cells, which indicates a cell phenotype most likely to promote fibrotic disease. Mesenchymal transformation due to altered ECM was found to depend on cell–ECM bond strength and extracellular signal‐regulated protein kinases 1/2 signaling. Determining the environmental conditions that induce and promote EndMT, and the subsequent behavior of mesenchymally transformed cells, will advance understanding on the role of endothelial cells in tissue regeneration or disease progression. © 2017 Wiley Periodicals Inc. J Biomed Mater Res Part A: 105A: 2729–2741, 2017.